Effects of a single bout of short-duration high-intensity and long-duration low-intensity exercise on insulin resistance and adiponectin/leptin ratio. Issue 1 (January 2021) - Kao, Hsiang-Han; Hsu, Hua-Shui; Wu, Tai-Hsien; Chiang, Hui-Fen; Huang, Hui-Ying; Wang, Hui-Ju; Yang, Gloria; Lin, Wen-Yuan
Abstract: Objectives: Moderate-intensity exercise improves insulin sensitivity, which may depend on the intensity, duration, and frequency of exercise. We examined the effects of a single bout of short-duration high-intensity exercise (HIE) and long-duration lowintensity exercise (LIE) on insulin sensitivity and the adiponectin/leptin ratio in individuals with different body mass indices (BMIs) who do not exercise regularly. Methods: We enrolled 42 healthy volunteers aged 20–64 years and divided them into two groups based on BMI: BMI <24 kg/m 2 and BMI ≥27 kg/m 2 . They were randomly assigned to either the short-duration (20 min) HIE (70%–80% heart rate reserve, HRR) or long-duration (60 min) LIE training groups (30%–40% HRR). Glucose, insulin, adiponectin, and leptin levels were assessed before training and at 0, 30, 60, and 120 min after training. Results: We finally analyzed 27 normal weight and 9 obese individuals. No significant differences were observed in the baseline information of both BMI groups. Homeostatic model assessment for insulin resistance significantly improved for both exercise patterns in the normal weight group and for the HIE pattern in the obese group (P < 0.01), whereas the adiponectin/leptin ratio increased significantly only among normal weight participants with the LIE intervention. Conclusion: Both exercise patterns in BMI <24 kg/m 2 and BMI ≥27 kg/m 2 benefit on insulin resistance. Therefore, people can choose the way they can fit to improve insulin resistance both short-duration high-intensity exercise and long-duration low-intensity exercise.